Low Serum Testosterone in Men with Newly Diagnosed Androgen-Deprivation Therapy-Naïve Prostate Cancer and Its Relationship to Cardiovascular Risk Factors: A RADICAL-PC Substudy. Issue 5 (3rd May 2022) - Pinthus, Jehonathan H.; Duivenvoorden, Wilhelmina C. M.; Klotz, Laurence; Mukherjee, Som D.; Siemens, D. Robert; Niazi, Tamim; Fradet, Vincent; Foster, William; Duceppe, Emmanuelle; Taussky, Daniel; Hamilton, Robert; Lavallée, Luke; et al.
Abstract : Purpose: Cardiovascular disease is a common cause of death in prostate cancer patients. Low testosterone is associated with increased cardiovascular risk in the general male population. We investigated the relationship between serum testosterone, cardiovascular disease and risk factors in androgen-deprivation therapy-naïve prostate cancer patients. Materials and Methods: We performed a cross-sectional analysis of a subgroup of 1, 326 androgen-deprivation therapy-naïve men from RADICAL-PC (Role of Androgen-Deprivation Therapy In CArdiovascular Disease—A Longitudinal Prostate Cancer study) in whom serum testosterone was measured at baseline. RADICAL-PC is a prospective multicenter cohort study of men (2, 565) enrolled within 1 year of prostate cancer diagnosis, or within 6 months of commencing androgen-deprivation therapy for the first time. Cardiovascular risk factors, cancer characteristics and total serum testosterone were collected at baseline. Low testosterone was defined as total serum testosterone <11 nmol/L (<320 ng/dL). A Framingham cardiovascular risk score ≥15 was considered high risk for future cardiovascular events. We performed logistic regression to calculate odds ratios for the association between testosterone and cardiovascular risk. Results: Among 1, 326 participants (median age 67 years, range 45–93), 553 (42%) had low testosterone. Low testosterone was associated with existing cardiovascular disease, diabetes, elevated hemoglobin A1c, obesity, hypertriglyceridemia, low high-density lipoprotein cholesterol, hypertension and Framingham score >15. Among patients with low testosterone, the odds ratio for high cardiovascular risk was 1.33 (1.02–1.73) after adjusting for ethnicity, education, alcohol use, cancer characteristics, physical activity and body mass index. Conclusions: Among androgen-deprivation therapy-naïve prostate cancer patients, low testosterone is common and associated with increased cardiovascular risk factors.